Merek Dagang dalam Perspektif Fikih Islam - Husnul Haq (IAIN Purwokerto, 2022)
This research aims at studying the trademark from fiqh perspective. It looks into the definition of the trademark, its functions, and forms. At the same times, it studies the main concepts which can be considered as an introduction to this study and an explanantion of al-Takyif al-fiqhi (the adaptation of doctrinal statement). This research relies on analytic and critical methodologies, as well as comparative methodology to arrive at its conclusions. Among these conclusions are that trademark from the fiqh perspective is considered as property, benefit, and right that are guarded by shara’. This research demonstrates that there are many kinds of trademark infringement, such as counterfeit, imitation, trading in counterfeit or imitative goods, etc. Therefore, ta’zir can be considered as the most suitable punishment for trademark infringement. This study will also find out whether or not zakat of it should be taken from its net yield by 2,5% after hawl.